2018
DOI: 10.1080/13607863.2018.1468411
|View full text |Cite
|
Sign up to set email alerts
|

Association between polypharmacy and dementia – A systematic review and metaanalysis

Abstract: Pooled risk estimates from this meta-analysis showed that polypharmacy was associated with dementia. Although the causality of the relationship cannot be concluded from this analysis, the finding encourages the use of multidimensional assessment tools for dementia that includes the number of medications as a component.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 69 publications
5
35
0
Order By: Relevance
“…Epidemiological study has indicated that approximately half of the elderly adult population is subjected to polypharmacy 5 . Polypharmacy is a critical problem for elderly adults because it decreases medication adherence, 6 and increases both healthcare costs and the risk of adverse drug events, such as falls and fractures, 7 cognitive decline, 8 drug‐induced parkinsonism 9 and potentially inappropriate medicines (PIMs) 10 . Some medications cause side effects that appear to be symptoms of poor oral health, such as dry mouth, 11 oral ulcers 12 and taste disorders 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological study has indicated that approximately half of the elderly adult population is subjected to polypharmacy 5 . Polypharmacy is a critical problem for elderly adults because it decreases medication adherence, 6 and increases both healthcare costs and the risk of adverse drug events, such as falls and fractures, 7 cognitive decline, 8 drug‐induced parkinsonism 9 and potentially inappropriate medicines (PIMs) 10 . Some medications cause side effects that appear to be symptoms of poor oral health, such as dry mouth, 11 oral ulcers 12 and taste disorders 13 .…”
Section: Introductionmentioning
confidence: 99%
“…These studies have revealed various complications due to polypharmacy, such as adverse drug events, 4,5 falls 7,11 and increased mortality. 12,13 However, to our knowledge, few studies have predicted the length of hospitalization using patient characteristics and medical history. In the current study, polypharmacy at admission was identified as a predictor of prolonged hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Although we are not aware of any studies that have identified an association between polypharmacy and AD severity, there have been some recent studies showing that polypharmacy is a risk factor for dementia. 33,34 Other studies have also correlated polypharmacy with prescription of PIMs 1 and occurrence of PIIs. 3 Presence of these factors is associated with increased mortality among elderly people.…”
Section: Discussionmentioning
confidence: 99%